English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-20 03:57:08 · 13 answers · asked by white_cocoa342 1 in Science & Mathematics Mathematics

13 answers

Do you mean: (n+1)^2 = 4 ("n+1" is raised to the power of 2)?
Or, (n+1)(2) = 4? I'll solve both equations.

1. (n+1)^2 = 4
First: eliminate the exponent by finding the square root of both sides...

V`(n+1)^2 = +/- V`4

V`(n+1)(n+1) = +/- V`4

a) n + 1 = 2
First: solve for "n" by isolating it on one side
Sec: subtract "1" from both sides (when you move a variable to the opposite side-use the opposite sign)...

n + 1 - 1 = 2 - 1
n = 1

b). n + 1 = - 2
n + 1 - 1 = - 2 - 1
n = - 3

Solutions: 1 and - 3

2. (n+1)(2) = 4

First: eliminate the parenthesis > multiply the outer term with the terms in the parenthesis...

2(n) + 2(1) = 4
2n + 2 = 4

Sec: subtract "2" from both sides...

2n + 2 - 2 = 4 - 2
2n = 2

Third: solve for "n" by isolating it on one isde > divide both sides by 2...

2n/2 = 2/2
n = 1

2007-01-20 04:33:33 · answer #1 · answered by ♪♥Annie♥♪ 6 · 1 0

n = 1

2007-01-20 12:00:46 · answer #2 · answered by JonnyNewbrook 2 · 0 0

If this is a multiplication by 2 you get n+1=2==> n=1
if it is (n+1)^2 you get n+1= +-2 so n can be 1 or -3

2007-01-20 12:03:28 · answer #3 · answered by santmann2002 7 · 0 0

n=1 :)

2007-01-20 12:00:04 · answer #4 · answered by Ty 2 · 0 0

I'm assuming you mean (n + 1) squared, considering how nicely the answer works out, and how the 2 is to the right of (n + 1) {since constants are typically written in FRONT of bracketed binomials.}

(n + 1)^2 = 4

One quirk you have to know about taking the square root of both sides of an equation is that you ALWAYS have to add "Plus or minus", or +/-, to the right hand side upon doing so. That's what we have to do:

n + 1 = +/- 2

Moving the 1 to the right hand side,

n = -1 +/- 2

This leads to two values:

n = -1 + 2, and
n = -1 - 2

n = {1, -3}

2007-01-20 12:02:12 · answer #5 · answered by Puggy 7 · 0 0

2n+2 = 4, 2n = 2 n=1

2007-01-20 12:07:08 · answer #6 · answered by physicist05 2 · 0 0

2n +2 = 4
2n+2-2 = 4-2
2n = 2
n = 1

2007-01-20 12:16:31 · answer #7 · answered by tennisfreak 1 · 0 0

(n+1)2 = 4
2n + 2 = 4 | -2
2n = 2 | /2
n = 1

2007-01-20 12:00:56 · answer #8 · answered by eva 3 · 0 0

2n+2=4
-2 -2

2n = 2
n=1

2007-01-20 12:04:03 · answer #9 · answered by a c 7 · 0 0

Are looking for either this:
(n+1)^2=4 or this:
2n+2=4

I will solve for it either way:
n^2+2n+1=4
n^2+2n-3=0
(n+3)(n-1)=0
n=-3 and 1

2n+2=4
2n=2
n=1

I hope this helps!

2007-01-20 12:40:43 · answer #10 · answered by Anonymous · 0 0

fedest.com, questions and answers